2014
DOI: 10.1016/j.cognition.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

In the attraction, compromise, and similarity effects, alternatives are repeatedly compared in pairs on single dimensions

Abstract: In multi-alternative choice, the attraction, compromise, and similarity effects demonstrate that the value of an alternative is not independent of the other alternatives in the choice-set. Rather, these effects suggest that a choice is reached through the comparison of alternatives. We investigated exactly how alternatives are compared against each other using eye-movement data. The results indicate that a series of comparisons is made in each choice, with a pair of alternatives compared on a single attribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
163
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(175 citation statements)
references
References 25 publications
9
163
3
Order By: Relevance
“…After several repetitions, participants report a preference bias for the longer-presented face, indicating that manipulation of gaze can directly influence preference decisions. While the gaze cascade effect has been observed in other studies examining preference choice (Noguchi and Stewart, 2014; Simion and Shimojo, 2006), the effect may also extend to other types of visual decision-making tasks (Fiedler, 2012; Glaholt and Reingold, 2009; Wiener et al, 2011). …”
Section: Introductionmentioning
confidence: 67%
“…After several repetitions, participants report a preference bias for the longer-presented face, indicating that manipulation of gaze can directly influence preference decisions. While the gaze cascade effect has been observed in other studies examining preference choice (Noguchi and Stewart, 2014; Simion and Shimojo, 2006), the effect may also extend to other types of visual decision-making tasks (Fiedler, 2012; Glaholt and Reingold, 2009; Wiener et al, 2011). …”
Section: Introductionmentioning
confidence: 67%
“…(One of many reasons to expect it does: Firms pay significant money to ensure product placement at eye-level. See Noguchi & Stewart, 2014 for an investigation of how gaze transitions relate to context effects.) Most cognitive models do not have much to say about these issues, but could, and doing so would both increase their relevance for consumer choice and their ability to be applied in other choice domains, such as political science or health.…”
Section: Consumer Choice In Contextmentioning
confidence: 98%
“…The way information is sampled can influence choice behavior in perceptual tasks, value-based decision making and experiential risky choice paradigms (Glaholt & Reingold, 2009Hills & Hertwig, 2010;Krajbich et al, 2010Krajbich et al, , 2015Krajbich & Rangel, 2011;Noguchi & Stewart, 2014;Russo & Leclerc, 1994;Shimojo et al, 2003). Computational models of decision making typically focus on the overall choice, given that a certain amount of information is available to the decision maker.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a great deal of interest in the relationship between gaze behavior and decision making (Glaholt & Reingold, 2009;Krajbich et al, 2010Krajbich et al, , 2015Krajbich & Rangel, 2011;Noguchi & Stewart, 2014;Russo & Leclerc, 1994;Shimojo et al, 2003). Specifically, it has been shown that the option fixated for longer and fixated last is more likely to be chosen (Glaholt & Reingold, 2009;Krajbich et al, 2010;Krajbich & Rangel, 2011;Shimojo et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation